Science TQM, New Quality Management Principle: The Quality Management Strategy of Toyota - Kakuro, Amasaka (Bentham Science Publishers, 2012)
'The Japanese management technology that made the biggest impact on the world in the second half of the 20th century were: the Toyota Production System, often also referred to as to Just-In-Time (JIT), which is the most famous Japanese production system; Total Quality Control (TQC) and Total Quality Management (TQM). However, as these management technologies became practiced as'lean systems'around the world and were further developed and popularized, they lost their status as unique Japanese systems - and in recent years, the superior quality of Japanese products has rapidly lost ground. As we enter a new era of remarkably competitive technological innovation (figuratively referred to as'global quality competition'), there is a strong desire for a codified management system that overhauls Japanese management techniques once again and updates them for the next generation. Executives and managers are concerned with generating rational management outcomes through Customer-first Quality Management.